Systematic Literature Review: Public Understanding of Artificial Intelligence Amid the Development of Digital Technology - Gesang Wicaksono Bumi; Dimas Febriawan (Devotion : Journal of Research and Community Service, 2026)
The rapid development of Artificial Intelligence (AI) in the era of digital transformation has driven increased use of AI-based technologies in various aspects of life. The presence of AI on social media platforms, in the education sector, the workplace, and digital services has made public interaction with this technology increasingly intense. However, the level of public understanding of AI varies and is influenced by social and psychological factors, as well as digital literacy levels. This research aims to analyze public understanding of AI based on previous studies and to identify public perceptions regarding the benefits and risks of AI amidst the dynamics of digital development. The method used was a Systematic Literature Review (SLR) with a qualitative approach through the collection and analysis of national and international journals published between 2020 and 2026. Literature selection was based on topic relevance, publication quality, and alignment with the research focus. The findings indicate that the public generally views AI positively, as it is perceived to enhance efficiency, productivity, and ease of access to information. However, there are also concerns regarding ethical issues, data privacy, reliance on technology, and the potential displacement of human labor. This study confirms that AI literacy and an understanding of digital technology are key factors in shaping public acceptance of AI developments in the digital age.